The Role of Green Sukuk for Sustainable National Development: Peran Green Sukuk terhadap Pembangunan Nasional yang Berkelanjutan - Hiljannah, Zalfa Zahirah; Desfiansyah, Fadlan; Putra, Anggi Tryfinza; Sarjono, Oka Raditya (JURNAL EKONOMI SYARIAH, 2023)
In this increasingly advanced era, sukuk has experienced more innovative developments with the emergence of interesting ideas in the form of green sukuk or green bonds. The issue of sustainability is being discussed more frequently due to its positive impact on the environment and future livelihoods. However, there are still individuals who are not fully aware of the importance of this concept, which can pose a serious threat to future survival. Therefore, the momentum of the sustainability movement should receive attention from the entire society, gradually understanding and implementing the concept of "sustainability" in every development action, both in environmental and social contexts. Thus, green sukuk instruments provide various benefits, including contributing to environmental preservation and indirectly involving the community in active and tangible national development. The objective of this research is to determine the extent of the role of green sukuk in sustainable national development. This research utilizes a descriptive qualitative approach to analyze relevant literature data. The data sources that will be used include various academic literature, reports from relevant financial institutions and government agencies, as well as related publications from international organizations. Data analysis is conducted by identifying and analyzing the main themes that emerge from the relevant literature. Green Sukuk is an Islamic bond instrument that combines Sharia principles with green projects to finance efforts in climate change mitigation, climate adaptation, and biodiversity conservation. The issuance of Green Sukuk involves an issuer who issues debt certificates to investors, with the funds obtained specifically allocated to projects that meet green criteria. The funded projects encompass renewable energy sectors, energy efficiency, sustainable transportation, waste management, reforestation, as well as climate change mitigation and environmental conservation efforts. Green Sukuk offers benefits to the issuer in terms of obtaining funds from investors interested in sustainable investments, while investors can invest in projects that have a positive impact on the environment and society. The Indonesian government has supported the development of Green Sukuk as part of their commitment to sustainable development, attracting high interest from both domestic and international investors.